DETERMINASI KUALITAS LAPORAN KEUANGAN DI PEMERINTAH KABUPATEN KARANGASEM - Ni Wayan Wiriyantini; I Ketut Mustika (Universitas Triatma Mulya, 2021)
This study aims to analyze the effect of accounting understanding, the use of accounting information system technology, the effectiveness of the application of accrual-based government accounting standards on the quality of government financial reports in Karangasem Regency. As an illustration, the population is employees of Regional Apparatus Organizations (OPD) in Karangasem Regency, totaling 41 OPD consisting of regional secretariats, DPRD secretariats, regional inspectors, hospitals, 24 offices, 5 agencies, 8 sub-districts with a total sample of 95 people consisting of 41 Financial Administration Officers (PPK), 41 financial information system operators and 13 BPKAD staff. The data collection method used in this research is through the distribution of questionnaires/questionnaires. The data analysis technique in this research is quantitative statistical analysis using multiple linear regression model which is completed with SPSS. The results of hypothesis testing show that: 1). Accounting understanding has a positive and significant influence on the quality of the Karangasem Regency government's financial statements. This means that the better the employee's understanding of the accounting process, the quality of the resulting financial statements will increase. 2). The use of accounting information system technology has a positive and significant impact on the quality of the Karangasem Regency Government's financial reports. This means that the better the utilization and use of accounting information systems and information technology in the process of preparing financial statements, the better the quality of the financial reports produced. and 3). The effectiveness of the application of accrual-based government accounting standards has a positive and significant effect on the quality of the Karangasem Regency Government's financial reports. The application of good and consistent accounting standards will have an impact on improving the quality of financial reports and errors in the presentation of financial statements can be avoided